A Educação Estética do Homem - Carvalho, Nazaré Cristina (Revista Cocar, 2012)
SCHILLER, Friedrich. A Educação Estética do Homem. São Paulo: Ed. Iluminuras, 1995. The Aesthetic Education of Man SCHILLER, Friedrich. The Aesthetic Education of Man. São Paulo: Ed. Iluminuras, 1995